Developing a framework for the effective functionality of LED initiatives in Helao Nafidi Town Council - Shiwayu, Eliud Mandume; Sifani, John; Haufiku, Isidor (Papanda Publishier, 2025)
The main objective of this study was to develop a framework for the effective functionality of LED initiatives in local governments (LGs) in Namibia (a developing country) and elsewhere globally. The effectiveness of LED initiatives represents informative and integrated understanding, intervention strategies, capital funds, and a framework aimed at MDGs and SDGs which combine environmental, economic, social, institutional, and political aspects by identifying their interlinkages in realizing the SDGs in LGs. The purpose of this study is to develop a framework for the effective functionality of LED initiatives in HNTC. The theoretical framework has been drawn out to make its research propositions within an active application framework of stakeholders theory. The study used a stakeholders theory (ST) which provides a framework for exploring the processes of effective interventions of stakeholders in a management sense, and the questionnaires, interview guide, and focus group discussions (FGDs) were designed in relation to the objectives of this study. The data was collected through mixed method research (MMR) and was analyzed by using MSE (for quantitative data) and ATLAS. ti (for qualitative data) which provided relevant analysis for the data. The framework developed in this study indicates that the LED process is dominated or influenced by both internal and external stakeholders regarding intervention strategies to ‘’deal with’’ toward sustainable measurements and minimal standards for a developed conceptual framework for LED initiative.